Perampanel Improves Cortical Myoclonus and Disability in Progressive Myoclonic Epilepsies: A Case Series and a Systematic Review of the Literature - Assenza, Giovanni (Front Neurol, 2021)
Introduction: Progressive myoclonic epilepsies (PMEs) are a heterogenous group of genetic diseases presenting with epilepsy, cognitive impairment, and severe action myoclonus, which can severely affect daily life activities and independent walking ability. Perampanel is a recent commercially available antiseizure medication with high efficacy against generalized seizures. Some reports supported the role of perampanel in ameliorating action myoclonus in PMEs. Here, we aimed to describe a case series and provide a systematic literature review on perampanel effects on PMEs. Methods: We report the perampanel effectiveness on myoclonus, daily life activities, and seizures on an original Italian multicenter case series of 11 individuals with PMEs. Then, using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines, we performed a systematic review on perampanel effect on myoclonus and disability in PMEs. We searched PubMed, Scopus, and Google Scholar articles on perampanel and PMEs up to June 2020. No prospective trials were found. We reviewed 11 case series manuscripts reporting 104 cases of different PMEs. Results: Here, we are reporting the effectiveness of perampanel in five individuals affected by Unverricht–Lundborg disease, three by Lafora disease, two by sialidosis, and one by an undetermined PME. Nine out of 11 individuals improved their disability related to the action myoclonus (two with Lafora disease did not). Among the 104 persons with PMEs collected by the systematic review, we found that more than half of the patients receiving perampanel exhibited an amelioration of action myoclonus and, consequently, of their independence in daily life activities. The Unverricht–Lundborg disease seemed to show the best clinical response to perampanel, in comparison with the other more severe PMEs. A significant seizure reduction was achieved by almost all persons with active epilepsy. Only 11% of PME patients dropped out due to inefficacy. Conclusions: Perampanel demonstrated a beneficial effect with regard to action myoclonus, disability, and seizures and was well-tolerated in people with PMEs, independently from their genetic diagnosis. Given the limited scientific evidence, broader prospective trials should be encouraged.